Students translation habituation in learning - Arif Hidayat; Fachri Helmanto (Mitra Palupi, 2021)
Background: Information accessed by students does not rule out the possibility of a number of local and foreign languages. Students optimize the use of smartphones by scanning certain pages in foreign books. Purpose: this study aims to reveal the phenomena that encourage changes in students' translation habituation in learning. Design and methods: This research was conducted using a descriptive analysis method, by conducting a survey of undergraduate students at 6 campuses. The data in this study were in the form of a questionnaire and a number of documents from journals and books. The valid data are then analysed to draw generalizations. Results: This study reveals the habituation of using machine translators that are commonly used by students. This translation habituation has two sides, 1) lecture assignments that require information or those that are required to use English can be carried out and 2) students lack information due to lack of understanding of knowledge about the quality of translation.